Investigation of drying behavior of glutinous rice (Oryza sativa var. glutinosa) in a fixed-bed dryer - Bathumaly, Sangitha; Che Man, Hasfalina; Hashim, Norhashila; Omar, Rozita; Abdul Hamid, Mohamad Rezi (Gadjah Mada University, 2025)
Small-scale glutinous rice processing facilities often rely on manual drying methods, with drying conditions typically determined by experience. Establishing an accurate drying profile of glutinous rice allows for optimal selection of drying conditions. This contribution investigated glutinous rice drying behaviors in fixed bed dryers at temperatures 40°C, 50°C, and 60°C. The Page model was determined to be the best-fit thin layer model for describing glutinous rice drying with R2 of 0.953 (50°C). Experimentally determined drying information was fed into the Aspen Plus V14 simulator to produce a digital version of glutinous rice drying process. A combined constant and falling rate mass transfer coefficient specified in the process simulator produced a simulation output close to that of the Page model with an R2 of 0.9843. Modeling and digitalization of glutinous rice drying in this work are instrumental to accurately predict the drying performance of glutinous rice or other food grains.